A survey on current practices, needs, responsibilities and preferences for knowledge dissemination in the field of injury and illness prevention among competitive snow sports stakeholders - Monsonís, O. B.; Spörri, J.; Gouttebarge, V.; Bolling, C.; Verhagen, E. (Sports Medicine - Open, 2025)
Background Injury and illness prevention practices in competitive snow sports must be better understood among stakeholders. In particular, there is a need for a greater understanding of what context-specific stakeholders require for prevention. Therefore, this study surveyed stakeholders` current practices, needs, responsibilities and knowledge dissemination preferences related to injury and illness prevention in competitive snow sports and described the main commonalities and differences between stakeholder groups.